Membedah Mekanisme Perencanaan Keuangan Desa:Antara Regulasi, Praktik Teknis, dan Realitas Lapangan di Desa Pakusari - Ulfi Maratul Azizah; Vanisa Nia Nur Ramadhani; Fanesya Sintya Bella; Siti Anisa; Oryza Ardhiarisca; Prillinaya Yudhistira (MUARA EKONOMI : Jurnal Ilmiah Ilmu Ekonomi, Manajemen & Bisnis, 2025)
This research aims to analyze the financial management planning process of Pakusari Village and assess its conformity with the provisions of Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Financial Management. This research uses qualitative methods with a case study approach. Data was obtained through in-depth interviews, observation and documentation with the main informants, namely KAUR Finance and KAUR Pakusari Village Planning. The results of the research show that the financial management planning of Pakusari Village is in accordance with Permendagri Number 20 of 2018 and is carried out in a participatory, transparent and accountable manner, including in terms of document adjustments to regulations. Obstacles such as delays in proposals can be overcome through coordination with village officials. However, it was found that there were duplicate tasks due to limited human resources in Pakisari village, where the preparation of the RPJMDes and RKPDes was mostly carried out by the Head of Finance. This finding shows that village governance is running well, but in terms of the division of tasks and effectiveness it still needs to be strengthened further. The limitation of this research lies in the fact that the object studied in this research only focuses on one village so the results cannot be generalized. Further studies can be carried out in other villages to provide results and a broader picture regarding the implementation of village financial planning